Endoscopic Ultrasound-Guided Gastrojejunostomy for Superior Mesenteric Artery Syndrome Secondary to Rapid Weight Loss. Issue 10 (6th October 2022) - Storm, Andrew C.; Mahmoud, Tala; Akiki, Karl; Law, Ryan J.
ABSTRACT: A 19-year-old man diagnosed with diffuse large B-cell lymphoma undergoing chemotherapy presented for recurrent emesis and weight loss. Imaging studies of the abdomen demonstrated features of superior mesenteric artery syndrome. The patient deferred conservative treatment options and was deemed not to be a surgical candidate. Endoscopic ultrasound-guided gastroenterostomy using a lumen-apposing metal stent was performed to bypass the obstruction. Subsequently, the patient's oral intake and weight significantly improved. The stent was removed 6 months after placement with resolution of superior mesenteric artery syndrome symptoms.